Perceived school climate and problematic internet use among adolescents: Mediating roles of school belonging and depressive symptoms. (November 2020) - Zhai, Boyu; Li, Dongping; Li, Xian; Liu, Yuxiao; Zhang, Jingyi; Sun, Wenqiang; Wang, Yanhui
Highlights: There is an urgent need to identify the mechanisms of adolescent PIU. Perceived school climate (PSC) was negatively associated with PIU. School belonging and depressive symptoms mediated the above link in a parallel way. PSC was also related to PIU via school belonging and depressive symptoms, serially. Abstract: Prior studies have found that a positive school climate can prevent adolescents from developing problematic Internet use (PIU), yet gaps remain in identifying the proximal mechanisms. Guided by social control theory and the self-medication hypothesis, this study examined the mediating roles of adolescents' sense of school belonging and depressive symptoms in the relationship between perceived school climate (PSC) and adolescent PIU. A total of 2, 758 adolescents ( M age  = 13.53 years; SD  = 1.06) were surveyed from 10 middle schools in southern China. Participants completed a series of questionnaires, including Perceived School Climate Scale, School Belonging Scale, Children's Depression Inventory, and Internet Addiction Diagnostic Questionnaire. We controlled for several covariates, including demographic variables and family functioning, for conservative predictions. Multiple mediation analysis revealed that: (a) PSC was negatively associated with PIU; (b) both school belonging and depressive symptoms mediated the link between PSC and PIU; and (c) a serial indirect pathway (i.e., PSC → school belonging → depressive symptoms → PIU) emerged. These findings were robust across different gender, age, socioeconomic status, and family functioning subgroups. These findings point to potential targets in the prevention and intervention of adolescent PIU.